2018
DOI: 10.5114/ceji.2018.74872
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of selected pro- and anti-inflammatory cytokines in patients with multiple injuries in the early period after trauma

Abstract: IntroductionSevere trauma causes damage to the protective barriers of the organism, and thus activates immunological reaction. Among substances secreted during this process pro-inflammatory cytokines are of high importance.The aim of the studySevere trauma causing multiple injuries is more likely to lead to particularly intensive inflammatory reaction, which can sometimes lead to serious complications, even life-threatening. The aim of the study is to determine those parameters which may serve as predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The explanation for that is that the main difference between male and female patients is represented by certain hormonal levels, namely estrogen, progesterone, and testosterone, and these hormones have no effect on the level of inflammatory mediators [5]. The current study showed no significant correlation between any of the cytokines and age of the patients which are in agreement with Gołąbek-Dropiewska et al [21]. The explanation for the lack of significant correlation between these cytokines and the age of the patient is most likely due to a relatively small sample size; however, substantial amount of published literature documents the negative correlation between age and immune markers due to the concept of aging of the immune system [22].…”
Section: Discussionsupporting
confidence: 90%
“…The explanation for that is that the main difference between male and female patients is represented by certain hormonal levels, namely estrogen, progesterone, and testosterone, and these hormones have no effect on the level of inflammatory mediators [5]. The current study showed no significant correlation between any of the cytokines and age of the patients which are in agreement with Gołąbek-Dropiewska et al [21]. The explanation for the lack of significant correlation between these cytokines and the age of the patient is most likely due to a relatively small sample size; however, substantial amount of published literature documents the negative correlation between age and immune markers due to the concept of aging of the immune system [22].…”
Section: Discussionsupporting
confidence: 90%
“…31 Plasma CRP concentration was significantly elevated in all four trauma groups. Golabek-Dropiewska et al 20 found that there was a correlation between elevated CRP level and the occurrence of infectious complications in severely injured trauma patients. While, Alper et al 32 demonstrated that mean CRP on admission was significantly higher in trauma patients compared with controls, CRP did not directly correlate with ISS and therefore was not helpful in predicting injury severity or outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of cytokines in the inflammatory response is well described as they activate, modulate, and inhibit inflammation in response to tissue damage, but their role in the bone marrow response to anemia is not as well understood. 20 This study was limited by small sample sizes, data from a single institution, and the lack of serial biochemical peripheral blood analyses. Although sample sizes were small, the results suggest that enrollment was adequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] IL-6 upregulates hepcidin production, leading to the sequestration of iron in macrophages, and also activates secretion of CRP. 20,21 Norepinephrine, a key modulator of hematopoietic progenitor mobilization and an inhibitor of bone marrow erythroid cell growth at high levels, also directly stimulates IL-6 release. 22 IL-1b and IL-6 levels have also been found to be increased early after traumatic brain injury, and there are marked alterations in the NO pathway after HS, along with enhanced formation of NO after systemic inflammation.…”
mentioning
confidence: 99%